Keterkaitan Kegiatan Konsumsi Dan Produksi Beras Dengan Pertumbuhan PDB Di Indonesia Dan Tiongkok - Muhammad Fikri aransyah (Jurnal Ekonomi Pembangunan, 2019)
Rice is a staple food for most Asian countries, and this can affect their economic performance. The dynamic regression model used in this study to investigate rice consumption or production can explain GDP growth. This research can provide relevant information to several parties such as researchers, academics, and institutions who tend to understand the rice market. This study examines whether rice consumption or rice production has a more considerable influence on the growth of Gross Domestic Product (GDP) in China and Indonesia between the 1990-2015 sample period. Empirical results show that rice production has a more significant influence than rice consumption on GDP growth. The Philips-Perron Root unit test shows that the country's GDP growth shows stationary at the first level and difference. In contrast, Indonesian rice production shows stationary at both levels and the primary difference, the other shows stationary at the first difference. Followed by the Granger causality test and variant decomposition, the results show a two-way relationship on the Chinese causality test.